Correlation of Reading Interests and Learning Motivation Toward Science Learning Outcomes - Wahyuni, Luh Tu Selpi; Japa, I Gusti Ngurah; Rati, Ni Wayan (Universitas Pendidikan Ganesha, 2020)
The low reading interests and learning motivation are the main problems in this study. That is due to the lack and support of families, schools, and communities to increase reading interests and learning motivation. This study aimed to determine the relationship of reading interests and learning motivation with the learning outcomes of science class V of primary school (elementary school). This type of research was ex-post facto research. The population of this study was 187 people. The sample was determined using random sampling techniques and 144 people were selected. The data collected was an interest in reading and student motivation to use questionnaire instruments and document recording. Data were analyzed by simple regression analysis, product-moment correlation, and multiple regression analysis. The results of the study obtained first, the value of r count 0.832> r table 0.138 which means that there is a significant relationship between reading interests and science learning outcomes. Second, the value of r count 0.988> r table 0.138 which means there is a significant relationship between learning motivation and science learning outcomes. Third, the value of r count 0.988> r table 0.164 which means that there is a significant relationship between reading interests and learning motivation with the results of learning science. The relationship shows that if students' reading interests and learning motivation is high, student learning outcomes tend to be high. It means that students' reading interests and learning motivation are very important to be instilled in the learning process to maintain good learning outcomes and improve student learning outcomes.